Lupus vulgaris on face: a case report - Nandakishore, Thokchom; S., Mrudula; Kongbam, Linda; Buchem, Chai E.; Rokita, Moirangthem; Anurag Srivastava (International Journal of Research in Dermatology, 2023)
Lupus vulgaris is the most common form of cutaneous tuberculosis in adults. Starts either by re-infection or by lymphatic or hematogenous spread or by direct spread in individuals with moderate immunity and high degree of tuberculin sensitivity. Females affected 2-3 times more, constitute 1-2% of all extra-pulmonary TB. Common sites involved are face and neck. We reported a case lupus vulgaris in a 52 year old female patient.